Comparison of margins and survival between transoral robotic surgery (TORS) and non-robotic endoscopic surgery for oropharyngeal cancer - Groysman, Matthew; Gleadhill, Claire; Baker, Audrey; Wang, Steven J.; Bearelly, Shethal (American journal of otolaryngology, 2023)
To evaluate the impact of transoral robotic surgery (TORS) and non-robotic transoral endoscopic surgery on margin positivity, rates of adjuvant therapy and survival in early stage oropharyngeal squamous cell carcinoma. Retrospective cohort review. The National Cancer Database was queried to form a cohort of patients with T1-T2 N0-N1 MO oropharyngeal squamous cell carcinoma who underwent TORS or Non-robotic endoscopic surgery from 2010 to 2015. Demographics, disease characteristics and rate of positive margin and adjuvant therapy were summarized. A binary logistic regression and a cox-proportional hazard model were performed to evaluate patient demographic, disease, and treatment factors that could predict margin positivity and survival respectively. 1026 patients received TORS treatment while 734 patients received non-robotic endoscopic primary surgery. Non-robotic surgery was more likely to have residual tumor (31.6 % of all cases) compared to TORS procedures (13.6 % of TORS cases); p < .0001. Non-robotic surgery more frequently had non-evaluable margins at 8.1 % compared to only 1.4 % of TORS cases (p < .0001). Non-robotic cases had a significantly higher proportion of patients receiving adjuvant radiotherapy and systemic therapy compared to TORS (66.4 % vs 51.3 % for radiotherapy; p < .0001 and 33.4 % vs 22.2 % for chemotherapy; p < .0001). There was no difference in mortality between the two modalities (non-robotic vs TORS, HR 1.357, 95 % CI 0.937–1.967). TORS and non-robotic surgery may have a similar impact on survival in early-stage OPSCC, but non-robotic surgery was found to have a higher likelihood of positive margins and a higher rate of adjuvant chemoradiation therapy.